Persistence of functional sympatholysis post-exercise in human skeletal muscle - Moynes, Jackie; Bentley, Robert F.; Bravo, Michael; Kellawan, J M.; Tschakovsky, Michael E. (Frontiers in Physiology, 2013)
Blunting of sympathetic vasoconstriction in exercising muscle is well established. Whether it persists during the early post-exercise period is unknown. This study tested the hypothesis that it persists in human skeletal muscle during the first 10 minutes of recovery from exercise. Eight healthy young males (21.4 ±0.8 yrs, SE) performed 7 minutes of forearm rhythmic isometric handgrip exercise at 15% below forearm critical power. In separate trials, a cold pressor test (CPT) of 2 min duration was used to evoke forearm sympathetic vasoconstriction in each of Rest (R), Steady State Exercise (Ex), 2-4 min Post Exercise (PEearly), and 8-10 min Post Exercise (PElate). A 7 min control exercise trial with no CPT was also performed. Exercising forearm brachial artery blood flow, arterial blood pressure, cardiac output, heart rate, forearm deep venous catecholamine concentration and arterialized venous catecholamine concentration were obtained immediately prior to and following the CPT in each trial. CPT resulted in a significant increase in forearm venous plasma norepinephrine concentration in all trials (P=0.007), but no change in arterialized plasma norepinephrine (P=0.32). CPT did not change forearm venous plasma epinephrine (P=0.596) or arterialized plasma epinephrine concentration (P=0.15). As assessed by the %reduction in forearm vascular conductance (FVC) the CPT evoked a robust vasoconstriction at rest that was severely blunted in exercise (R -39.9 ±4.6% vs. Ex 5.5 ±7.4%, P<0.001). This blunting of vasoconstriction persisted at PEearly (-12.3 ±10.1%, P=0.02) and PElate (-18.1 ±8.2%, P=0.03) post-exercise. In conclusion, functional sympatholysis remains evident in human skeletal muscle as much as 10 min after the end of a bout of forearm exercise. Persistence of functional sympatholysis may have important implications for blood pressure regulation in the face of a challenge to blood pressure following exercise.